The family experiment - Marrs, John (Freelance journalist) (Hanover Square Press, 2024)
When the company behind Virtual Children creates a reality TV show called "The Substitute," 10 couples compete to raise a Virtual Child from birth to age 18 in a nine-month period where the prize is the right to keep their virtual child or risk it all for the chance of a real baby.